Численный расчет электрических токов, магнитного поля и электродинамических сил в силовом трансформаторе в аварийных режимах с использованием MATLAB/SIMULINK и COMSOL - Подольцев, А.Д.; Конторович, Л.Н. (Технічна електродинаміка, 2011)
The approach to modeling of electromagnetic processes in power transformer at emergency operation is proposed. It consists of computation of instantaneous currents in transformer windings using Matlab/Simulink, computation of magnetic field in active zone of transformer and determination of distribution of electromagnetic forces in windings by means of code Comsol. Three types of emergency operation of the transformer as applied to specific power system (namely, connection of transformer with saturated core at no-load, single-phase and three-phase short-circuit in a load are considered. As shown, maximum value of forces in the windings are realized under condition of three-phase shortcircuit, and minimum - at single-phase short-circuit.